Ab Initio Study on the Vibrational and Electronic Properties of Radiation-Induced Defects in Potassium Bromide - Alexander Platonenko; Vladimir Pankratov; Eugene A. Kotomin; Alma Dauletbekova; Anatoli I. Popov (Crystals, 2024)
The vibrational and electronic properties of several basic radiation defects in potassium bromide are computed at the quantum mechanical level using a periodic supercell approach based on hybrid functionals, an all-electron Gaussian-type basis set, and the Crystalcomputer code. The exciton energy in alkali halides is sufficient to create lattice defects, such as F–H Frenkel defect pairs, resulting in a relatively high concentration of single defects and their complexes. Here, we consider eight defects: the electronic <semantics>F+</semantics>- and F-centers (bromine vacancy without and with trapped electrons) and their dimers; hole H-center (neutral bromine atom forming the dumbbell ion with a regular <semantics>Br−</semantics> ion.); <semantics>VK</semantics>-center (<semantics><msubsup>Br2−</msubsup></semantics> molecular ion consisting of a hole and two regular ions); and two complex <semantics><msubsup>Br3−</msubsup></semantics> defects, combinations of several simple defects. The local geometry and the charge- and spin-density distributions of all defects are analyzed. Every defect shows its characteristic features in Raman spectra, and their comparison with available experimental data is discussed.